Preparation method and application of lithium battery negative electrode binder

By using sulfonic acid functionalized COFs or carboxylic acid functionalized COFs and aqueous polyacrylic acid solution in the lithium battery negative electrode binder, the problems of poor mechanical strength, poor circulation performance and unstable processing of the existing lithium battery negative electrode binder are solved, and higher mechanical strength, cycle stability and battery capacity are achieved.

CN119614106APending Publication Date: 2025-03-14SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411753630.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium battery negative electrode binders have poor mechanical strength, poor circulation performance and unstable processing.

Method used

The preparation method of lithium battery negative electrode binder including 0.5%-1% sulfonic acid functionalized COFs or carboxylic acid functionalized COFs and 99%-99.5% aqueous polyacrylic acid solution was adopted. COFs were prepared by Schiff base reaction, and they were evenly dispersed in the aqueous polyacrylic acid solution by ultrasonic method.

Benefits of technology

The mechanical strength of the adhesive is improved, the impedance of the electrode sheet is reduced, the cycle stability and circulation efficiency of the lithium battery are improved, and the battery capacity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614106A_ABST
    Figure CN119614106A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a lithium battery negative electrode binder, belongs to the technical field of lithium batteries, and solves the technical problems that an existing lithium battery negative electrode binder is poor in mechanical strength, poor in cycle performance when applied to a lithium battery, unstable in processing and the like. According to the solution, the lithium battery negative electrode binder is prepared from the following components in percentage by mass: 0.5 to 1 percent of sulfonic acid functionalized COFs and 99 to 99.5 percent of polyacrylic acid aqueous solution or 0.5 to 1 percent of carboxylic acid functionalized COFs and 99 to 99.5 percent of polyacrylic acid aqueous solution; the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs are prepared from a first monomer and a second monomer through a Schiff base reaction; the preparation method of the lithium battery negative electrode binder comprises the following steps: 1) preparing sulfonic acid functionalized COFs or carboxylic acid functionalized COFs; 2) weighing polyacrylic acid and water, and uniformly mixing to prepare a polyacrylic acid aqueous solution; and 3) weighing 0.5%-1% of sulfonic acid functionalized COFs or carboxylic acid functionalized COFs prepared in the step 1), adding the weighed sulfonic acid functionalized COFs or carboxylic acid functionalized COFs into 99%-99.5% of a polyacrylic acid aqueous solution, and uniformly dispersing the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs in the polyacrylic acid aqueous solution in an ultrasonic manner. Compared with the prior art, the lithium battery negative electrode binder has the advantages that the lithium battery negative electrode binder is high in mechanical strength, a prepared electrode plate is small in impedance and not prone to breakage during processing, and a prepared lithium battery is high in cycling stability and cycling efficiency, large in capacity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a preparation method of a lithium battery negative electrode binder and an application thereof. Background Art

[0002] As new energy vehicles continue to increase their requirements for endurance, lithium battery negative electrode materials are also developing towards high specific capacity. Currently, lithium battery negative electrodes are mainly made of graphite and silicon materials, and the theoretical capacity of commercial graphite negative electrodes is only 372mAhg -1 , due to the extremely high specific capacity of silicon (Si), exceeding 3000mAhg -1 , which is ten times the capacity of graphite, so the use of silicon (Si) for negative electrodes has received widespread attention in the battery industry. Although the expansion of Si during repeated charge-discharge cycles has been identified as the main source of the insufficient cycle life of Si anodes, it is now clear that binders can significantly improve their cycle life. As one of the key components of lithium-ion batteries, binders have been used as early as the 1980s and have attracted widespread attention in the battery industry in recent years.

[0003] The binder in the electrode mainly binds the active material particles and the conductive agent together and adheres them to the current collector. It maintains the integrity of the electrode by maintaining sufficient contact between the active material and the current collector during repeated charge and discharge. However, the existing lithium battery negative electrode binders have poor mechanical strength, poor cycle performance when used in lithium batteries, and unstable processing. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art and solve technical problems such as poor mechanical strength of existing lithium battery negative electrode binders, poor cycle performance of lithium battery negative electrode binders used in lithium batteries, unstable processing, etc., the present invention provides a preparation method of a lithium battery negative electrode binder and its application.

[0005] The present invention is achieved through the following technical solutions.

[0006] The invention provides a lithium battery negative electrode binder, which comprises, by mass fraction, 0.5%-1% of sulfonic acid functionalized COFs and 99%-99.5% of a polyacrylic acid aqueous solution or 0.5%-1% of carboxylic acid functionalized COFs and 99%-99.5% of a polyacrylic acid aqueous solution, wherein the concentration of the polyacrylic acid in the polyacrylic acid aqueous solution is 2%.

[0007] Furthermore, the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs are prepared by a Schiff base reaction of a first monomer and a second monomer, wherein the first monomer is 2,4,6-trialdehyde phloroglucinol, and the second monomer is Wherein R is a carboxyl group or a sulfonic acid group.

[0008] Furthermore, the second monomer is 2,5-diaminobenzenesulfonic acid.

[0009] Furthermore, the second monomer is 2,5-diaminoterephthalic acid.

[0010] Furthermore, the second monomer is 4,4-diamino-3,3-biphenyldisulfonic acid.

[0011] Furthermore, the second monomer is 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid.

[0012] Further, the structural formula of the polyacrylic acid is

[0013] Further, the method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0014] 1) Preparation of sulfonic acid functionalized COFs or carboxylic acid functionalized COFs;

[0015] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0016] 3) Weigh 0.5%-1% of the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs prepared in step 1) and add them to 99%-99.5% polyacrylic acid aqueous solution, and uniformly disperse the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs in the polyacrylic acid aqueous solution by ultrasound.

[0017] Further, using the lithium battery negative electrode binder to prepare a lithium battery comprises the following steps:

[0018] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1 for coating, and the coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours before slicing to obtain a circular electrode sheet;

[0019] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0020] Furthermore, the active material in step S1 is silicon carbon-1200, and the conductive agent in step S1 is carbon nanotubes.

[0021] The beneficial effects achieved by the present invention are as follows: the present invention selects sulfonic acid functionalized COFs or carboxylic acid functionalized COFs and polyacrylic acid aqueous solution to prepare lithium battery negative electrode binder, the density of sulfonic acid functionalized COFs or carboxylic acid functionalized COFs is low, and the pores of sulfonic acid functionalized COFs or carboxylic acid functionalized COFs can also promote electrolyte wetting and ion transmission, which is beneficial to volume changes during charging and discharging, and improves the mechanical strength of the binder. Therefore, compared with traditional binders, the electrode sheet prepared by the lithium battery negative electrode binder with sulfonic acid functionalized COFs or carboxylic acid functionalized COFs as an auxiliary agent has low impedance and is not easy to break during processing; the lithium battery prepared by using the lithium battery negative electrode binder has high cycle efficiency, improved cycle stability, and increased battery capacity compared with traditional lithium batteries, and has broad application prospects.

[0022] Compared with the prior art, the present invention has the advantages of strong mechanical strength of the lithium battery negative electrode binder, small impedance of the prepared electrode sheet, not easy to break during processing, improved cycle stability and cycle efficiency of the prepared lithium battery, and large battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the synthesis of sulfonic acid functionalized COFs in Example 1 of the present invention;

[0024] Figure 2 is a schematic diagram of a cycle curve of a lithium battery in Example 1 of the present invention;

[0025] Figure 3 Schematic diagram of the synthesis of carboxylic acid functionalized COFs in Example 2 of the present invention;

[0026] Figure 4 is a schematic diagram of a cycle curve of a lithium battery in Example 2 of the present invention;

[0027] Figure 5 is a schematic diagram of the synthesis of sulfonic acid functionalized COFs in Example 3 of the present invention;

[0028] Figure 6 is a schematic diagram of a cycle curve of a lithium battery in Example 3 of the present invention;

[0029] Figure 7 Schematic diagram of the synthesis of carboxylic acid functionalized COFs in Examples 4 and 5 of the present invention;

[0030] Figure 8 It is a schematic diagram of the cycle curve of the lithium battery in Example 4 and Example 5 of the present invention. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0032] Example 1

[0033] like Figures 1 to 2 As shown, a lithium battery negative electrode binder includes 0.5% sulfonic acid functionalized COFs and 99.5% polyacrylic acid aqueous solution by mass fraction, the concentration of polyacrylic acid (PAA) in the polyacrylic acid aqueous solution is 2%, the sulfonic acid functionalized COFs is prepared by a first monomer and a second monomer through a Schiff base reaction, the first monomer is 2,4,6-trialdehyde phloroglucinol (TP), and the second monomer is 2,5-diaminobenzenesulfonic acid (DSB); the structural formula of the polyacrylic acid is

[0034] The method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0035] 1) Preparation of sulfonic acid functionalized COFs:

[0036] 0.15mmol, 31.52mg of 2,4,6-trialdehyde phloroglucinol, 0.225mmol, 42.35mg of 2,5-diaminobenzenesulfonic acid, 0.8ml of 1,3,5-trimethylbenzene, 0.2ml of 1,4-dioxane, and 0.1ml of acetic acid solution were weighed and added into an ampoule tube in sequence, and ultrasonic dispersion was performed until the system was uniform. Freeze-thaw cycles were performed for degassing 3 times under liquid nitrogen environment, and the ampoule tube was sealed and placed in a constant temperature oven at 120°C for reaction for 3 days, and a dark red precipitate was collected by suction, and then washed with tetrahydrofuran and extracted with Soxhlet for 24h, and finally dried under vacuum to obtain TP-DSB-COF;

[0037] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0038] 3) Weigh 0.5% of the TP-DSB-COF prepared in step 1) and add it to a 99.5% polyacrylic acid aqueous solution, and evenly disperse the TP-DSB-COF in the polyacrylic acid aqueous solution by ultrasonication. TP-DSB-COF has a low density, and the pores of TP-DSB-COF can also promote electrolyte wetting and ion transport, which is beneficial to volume changes during charge and discharge, and improves the mechanical strength of the adhesive.

[0039] The method of preparing a lithium battery using the lithium battery negative electrode binder comprises the following steps:

[0040] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1, deionized water is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on a copper foil using an automatic coating machine for coating. The active material is silicon carbon-1200, and the conductive agent is carbon nanotubes. The coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet. The diameter of the circular electrode sheet is 12 mm, and the loading amount of silicon carbon-1200 on the circular electrode sheet is 1.0-1.5 mg cm -2 Compared with traditional binders, the electrode sheets prepared by adding TP-DSB-COF additive to the lithium battery negative electrode binder have low impedance and are not easy to break during processing.

[0041] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0042] After the lithium battery was placed at room temperature for 8 hours, the battery was subjected to constant current charge and discharge tests using the Blue Dot test system. The voltage range was set to 0.01-1.5V (vs. Li / Li+). By setting different current densities and the number of cycles at different current densities, the cycle performance and rate performance of Silicon Carbon-1200 could be measured.

[0043] In the first five cycles, the initial charge and discharge capacity of the lithium battery was tested at a current density of 0.1C and the battery was activated. Then, the capacity and stability of the lithium battery were tested at a current density of 1.5C, as shown in Table 1.

[0044] Table 1 Cycle comparison of pure polyacrylic acid binder and lithium battery negative electrode binder with TP-DSB-COF additive

[0045]

[0046] As can be seen from Table 1, the addition of 0.5% TP-DSB-COF additive to the lithium battery negative electrode binder has a good improvement on the cycle stability of the battery compared with the pure polyacrylic acid binder, and the cycle efficiency is increased from 75.33% to 85.55%.

[0047] Example 2

[0048] like Figures 3 to 4As shown, a lithium battery negative electrode binder includes 1% carboxylic acid functionalized COFs and 99% polyacrylic acid aqueous solution by mass fraction, the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%, the carboxylic acid functionalized COFs is prepared by a first monomer and a second monomer through a Schiff base reaction, the first monomer is 2,4,6-trialdehyde phloroglucinol (TP), and the second monomer is 2,5-diaminoterephthalic acid (DAB); the structural formula of the polyacrylic acid is

[0049] The method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0050] 1) Preparation of carboxylic acid functionalized COFs:

[0051] 0.15mmol, 31.52mg of 2,4,6-trialdehyde phloroglucinol, 0.225mmol, 34.23mg of 2,5-diaminoterephthalic acid, 0.8ml of 1,3,5-trimethylbenzene, 0.2ml of 1,4-dioxane, and 0.1ml of acetic acid solution were weighed and added into an ampoule tube in sequence, and ultrasonic dispersion was performed until the system was uniform. Freeze-thaw cycle degassing was performed 3 times under liquid nitrogen environment, and the ampoule tube was sealed and placed in a constant temperature oven at 120°C for reaction for 3 days, and a dark red precipitate was collected by suction, and then washed with tetrahydrofuran and Soxhlet extraction was performed for 24h, and finally dried under vacuum to obtain TP-DSB-COF;

[0052] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0053] 3) Weigh 1% of the TP-DAB-COF prepared in step 1) and add it to a 99% polyacrylic acid aqueous solution, and evenly disperse the TP-DAB-COF in the polyacrylic acid aqueous solution by ultrasonication. TP-DAB-COF has a low density, and the pores of TP-DAB-COF can also promote electrolyte wetting and ion transport, which is beneficial to volume changes during charge and discharge, and improves the mechanical strength of the adhesive.

[0054] The method of preparing a lithium battery using the lithium battery negative electrode binder comprises the following steps:

[0055] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1, deionized water is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on a copper foil using an automatic coating machine for coating. The active material is silicon carbon-1200, and the conductive agent is carbon nanotubes. The coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet. The diameter of the circular electrode sheet is 12 mm, and the loading amount of silicon carbon-1200 on the circular electrode sheet is 1.0-1.5 mg cm -2 Compared with traditional binders, the electrode sheets prepared with lithium battery negative electrode binders with TP-DAB-COF additive have low impedance and are not easy to break during processing.

[0056] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0057] After the lithium battery was placed at room temperature for 8 hours, the battery was subjected to constant current charge and discharge tests using the Blue Dot test system. The voltage range was set to 0.01-1.5V (vs. Li / Li+). By setting different current densities and the number of cycles at different current densities, the cycle performance and rate performance of Silicon Carbon-1200 could be measured.

[0058] In the first five cycles, the initial charge and discharge capacity of the lithium battery was tested at a current density of 0.1C and the battery was activated. Then, the capacity and stability of the lithium battery were tested at a current density of 1.5C, as shown in Table 2.

[0059] Table 2 Cycle comparison of pure polyacrylic acid binder and lithium battery negative electrode binder with TP-DAB-COF additive

[0060]

[0061] It can be seen from Table 2 that the addition of 1% TP-DAB-COF additive to the lithium battery negative electrode binder has a good improvement on the cycle stability of the battery compared with the pure polyacrylic acid binder, and the cycle efficiency is increased from 75.33% to 91.81%.

[0062] Example 3

[0063] like Figures 5 to 6As shown, a lithium battery negative electrode binder includes 1% sulfonic acid functionalized COFs and 99% polyacrylic acid aqueous solution by mass fraction, the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%, the sulfonic acid functionalized COFs is prepared by a first monomer and a second monomer through a Schiff base reaction, the first monomer is 2,4,6-trialdehyde phloroglucinol (TP), and the second monomer is 4,4-diamino-3,3-biphenyldisulfonic acid (DSBP); the structural formula of the polyacrylic acid is

[0064] The method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0065] 1) Preparation of sulfonic acid functionalized COFs:

[0066] 0.1 mmol and 21.01 mg of 2,4,6-trialdehyde phloroglucinol, 0.15 mmol and 51.66 mg of 4,4-diamino-3,3-biphenyldisulfonic acid, 0.8 ml of 1,3,5-trimethylbenzene, 0.2 ml of 1,4-dioxane, and 0.1 ml of acetic acid solution were weighed and added into an ampoule tube in sequence, and ultrasonic dispersion was performed until the system was uniform. Freeze-thaw cycles were performed for degassing 3 times under liquid nitrogen environment, and the ampoule tube was sealed and placed in a constant temperature oven at 120°C for reaction for 3 days, and a dark red precipitate was collected by suction, and then washed with tetrahydrofuran and extracted with Soxhlet for 24 hours, and finally dried under vacuum to obtain TP-DSBP-COF;

[0067] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0068] 3) Weigh 1% of the TP-DSBP-COF prepared in step 1) and add it to a 99% polyacrylic acid aqueous solution, and evenly disperse the TP-DSBP-COF in the polyacrylic acid aqueous solution by ultrasonication. TP-DSBP-COF has a low density, and the pores of TP-DSBP-COF can also promote electrolyte wetting and ion transport, which is beneficial to volume changes during charge and discharge, and improves the mechanical strength of the adhesive.

[0069] The method of preparing a lithium battery using the lithium battery negative electrode binder comprises the following steps:

[0070] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1, deionized water is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on a copper foil using an automatic coating machine for coating. The active material is silicon carbon-1200, and the conductive agent is carbon nanotubes. The coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet. The diameter of the circular electrode sheet is 12 mm, and the loading amount of silicon carbon-1200 on the circular electrode sheet is 1.0-1.5 mg cm -2 Compared with traditional binders, the electrode sheets prepared with lithium battery negative electrode binders with TP-DSBP-COF additive have low impedance and are not easy to break during processing.

[0071] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0072] After the lithium battery was placed at room temperature for 8 hours, the battery was subjected to constant current charge and discharge tests using the Blue Dot test system. The voltage range was set to 0.01-1.5V (vs. Li / Li+). By setting different current densities and the number of cycles at different current densities, the cycle performance and rate performance of Silicon Carbon-1200 could be measured.

[0073] In the first five cycles, the initial charge and discharge capacity of the lithium battery was tested at a current density of 0.1C and the battery was activated. Then, the capacity and stability of the lithium battery were tested at a current density of 1.5C, as shown in Table 3.

[0074] Table 3 Cycle comparison of pure polyacrylic acid binder and lithium battery negative electrode binder with TP-DSBP-COF additive

[0075]

[0076] It can be seen from Table 3 that the addition of 1% TP-DSBP-COF additive to the lithium battery negative electrode binder has a good improvement on the battery capacity compared with the pure polyacrylic acid binder. Although the cycle efficiency of the lithium battery prepared by adding 1% TP-DSBP-COF additive to the lithium battery negative electrode binder dropped to 73.68% after 200 cycles, the battery capacity has always been higher than the lithium battery prepared by the pure polyacrylic acid binder.

[0077] Example 4

[0078] like Figures 7 to 8As shown, a lithium battery negative electrode binder includes 0.5% carboxylic acid functionalized COFs and 99.5% polyacrylic acid aqueous solution by mass fraction, the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%, the carboxylic acid functionalized COFs is prepared by a first monomer and a second monomer through a Schiff base reaction, the first monomer is 2,4,6-trialdehyde phloroglucinol (TP), and the second monomer is 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid (DABP); the structural formula of the polyacrylic acid is

[0079] The method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0080] 1) Preparation of carboxylic acid functionalized COFs:

[0081] 0.1 mmol and 21.01 mg of 2,4,6-trialdehyde phloroglucinol, 0.15 mmol and 40.84 mg of 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid, 0.8 ml of 1,3,5-trimethylbenzene, 0.2 ml of 1,4-dioxane, and 0.1 ml of acetic acid solution were weighed and added into an ampoule tube in sequence, and ultrasonic dispersion was performed until the system was uniform. Freeze-thaw cycles were performed for degassing 3 times under liquid nitrogen environment, and the ampoule tube was sealed and placed in a constant temperature oven at 120°C for reaction for 3 days, and a dark red precipitate was collected by suction, and then washed with tetrahydrofuran and extracted with Soxhlet for 24 hours, and finally dried under vacuum to obtain TP-DABP-COF;

[0082] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0083] 3) Weigh 0.5% of TP-DABP-COF prepared in step 1) and add it to 99.5% polyacrylic acid aqueous solution, and evenly disperse TP-DABP-COF in the polyacrylic acid aqueous solution by ultrasonication. TP-DABP-COF has a low density, and the pores of TP-DABP-COF can also promote electrolyte wetting and ion transport, which is beneficial to volume changes during charge and discharge, and improves the mechanical strength of the adhesive.

[0084] The method of preparing a lithium battery using the lithium battery negative electrode binder comprises the following steps:

[0085] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1, deionized water is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on a copper foil using an automatic coating machine for coating. The active material is silicon carbon-1200, and the conductive agent is carbon nanotubes. The coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet. The diameter of the circular electrode sheet is 12 mm, and the loading amount of silicon carbon-1200 on the circular electrode sheet is 1.0-1.5 mg cm -2 Compared with traditional binders, the electrode sheets prepared by adding TP-DABP-COF additive to the lithium battery negative electrode binder have low impedance and are not easy to break during processing.

[0086] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0087] After the lithium battery was placed at room temperature for 8 hours, the battery was subjected to constant current charge and discharge tests using the Blue Dot test system. The voltage range was set to 0.01-1.5V (vs. Li / Li+). By setting different current densities and the number of cycles at different current densities, the cycle performance and rate performance of Silicon Carbon-1200 could be measured.

[0088] In the first five cycles, the initial charge and discharge capacity of the lithium battery was tested at a current density of 0.1C and the battery was activated. Then, the capacity and stability of the lithium battery were tested at a current density of 1.5C, as shown in Table 4.

[0089] Table 4 Cycle comparison of pure polyacrylic acid binder and lithium battery negative electrode binder with TP-DABP-COF additive

[0090]

[0091] It can be seen from Table 4 that the addition of 0.5% TP-DABP-COF additive to the lithium battery negative electrode binder has a good improvement on the battery capacity compared with the pure polyacrylic acid binder. Although the cycle efficiency of the lithium battery prepared by adding 0.5% TP-DABP-COF additive to the lithium battery negative electrode binder dropped to 66.96% after 300 cycles, the battery capacity has always been higher than the lithium battery prepared by the pure polyacrylic acid binder.

[0092] Example 5

[0093] like Figures 7 to 8As shown, a lithium battery negative electrode binder includes 1% carboxylic acid functionalized COFs and 99% polyacrylic acid aqueous solution by mass fraction, the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%, the carboxylic acid functionalized COFs is prepared by a first monomer and a second monomer through a Schiff base reaction, the first monomer is 2,4,6-trialdehyde phloroglucinol (TP), and the second monomer is 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid (DABP); the structural formula of the polyacrylic acid is

[0094] The method is used to prepare a lithium battery negative electrode binder, comprising the following steps:

[0095] 1) Preparation of carboxylic acid functionalized COFs:

[0096] 0.1 mmol and 21.01 mg of 2,4,6-trialdehyde phloroglucinol, 0.15 mmol and 40.84 mg of 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid, 0.8 ml of 1,3,5-trimethylbenzene, 0.2 ml of 1,4-dioxane, and 0.1 ml of acetic acid solution were weighed and added into an ampoule tube in sequence, and ultrasonic dispersion was performed until the system was uniform. Freeze-thaw cycles were performed for degassing 3 times under liquid nitrogen environment, and the ampoule tube was sealed and placed in a constant temperature oven at 120°C for reaction for 3 days, and a dark red precipitate was collected by suction, and then washed with tetrahydrofuran and extracted with Soxhlet for 24 hours, and finally dried under vacuum to obtain TP-DABP-COF;

[0097] 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%;

[0098] 3) Weigh 1% of the TP-DABP-COF prepared in step 1) and add it to a 99% polyacrylic acid aqueous solution, and evenly disperse the TP-DABP-COF in the polyacrylic acid aqueous solution by ultrasonication. TP-DABP-COF has a low density, and the pores of TP-DABP-COF can also promote electrolyte wetting and ion transport, which is beneficial to the volume change during the charge and discharge process and improves the mechanical strength of the adhesive.

[0099] The method of preparing a lithium battery using the lithium battery negative electrode binder comprises the following steps:

[0100] S1: The active material, the lithium battery negative electrode binder and the conductive agent are mixed in a mass ratio of 7:2:1, deionized water is added, and the mixture is ground into a slurry with a certain fluidity. The slurry is evenly coated on a copper foil using an automatic coating machine for coating. The active material is silicon carbon-1200, and the conductive agent is carbon nanotubes. The coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet. The diameter of the circular electrode sheet is 12 mm, and the loading amount of silicon carbon-1200 on the circular electrode sheet is 1.0-1.5 mg cm -2 Compared with traditional binders, the electrode sheets prepared by adding TP-DABP-COF additive to the lithium battery negative electrode binder have low impedance and are not easy to break during processing.

[0101] S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

[0102] After the lithium battery was placed at room temperature for 8 hours, the battery was subjected to constant current charge and discharge tests using the Blue Dot test system. The voltage range was set to 0.01-1.5V (vs. Li / Li+). By setting different current densities and the number of cycles at different current densities, the cycle performance and rate performance of Silicon Carbon-1200 could be measured.

[0103] In the first five cycles, the initial charge and discharge capacity of the lithium battery was tested at a current density of 0.1C and the battery was activated. Then, the capacity and stability of the lithium battery were tested at a current density of 1.5C, as shown in Table 5.

[0104] Table 5 Cycle comparison of pure polyacrylic acid binder and lithium battery negative electrode binder with TP-DABP-COF additive

[0105]

[0106] It can be seen from Table 5 that the addition of 1% TP-DABP-COF additive to the lithium battery negative electrode binder has a good improvement on the cycle stability of the battery compared with the pure polyacrylic acid binder, and the cycle efficiency is increased from 75.33% to 88.22%.

[0107] The above describes in detail the implementation modes of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes. The implementation modes can still be changed within the knowledge scope of ordinary technicians in the field. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium battery negative electrode binder, characterized in that: The solution comprises, by mass fraction, 0.5%-1% of sulfonic acid functionalized COFs and 99%-99.5% of polyacrylic acid aqueous solution or 0.5%-1% of carboxylic acid functionalized COFs and 99%-99.5% of polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%.

2. A lithium battery negative electrode binder according to claim 1, characterized in that: The sulfonic acid functionalized COFs or carboxylic acid functionalized COFs are prepared by a first monomer and a second monomer through a Schiff base reaction, wherein the first monomer is 2,4,6-trialdehyde phloroglucinol, and the second monomer is Wherein R is a carboxyl group or a sulfonic acid group.

3. A lithium battery negative electrode binder according to claim 2, characterized in that: The second monomer is 2,5-diaminobenzenesulfonic acid.

4. A lithium battery negative electrode binder according to claim 2, characterized in that: The second monomer is 2,5-diaminoterephthalic acid.

5. A lithium battery negative electrode binder according to claim 2, characterized in that: The second monomer is 4,4-diamino-3,3-biphenyldisulfonic acid.

6. A lithium battery negative electrode binder according to claim 2, characterized in that: The second monomer is 4,4-diamino-1,1-biphenyl-3,3-dicarboxylic acid.

7. A lithium battery negative electrode binder according to claim 1, characterized in that: The structural formula of the polyacrylic acid is 8. A method for preparing a lithium battery negative electrode binder, characterized in that: The method for preparing a lithium battery negative electrode binder as claimed in any one of claims 1 to 7 comprises the following steps: 1) Preparation of sulfonic acid functionalized COFs or carboxylic acid functionalized COFs; 2) weighing polyacrylic acid and water and mixing them evenly to prepare a polyacrylic acid aqueous solution, wherein the concentration of polyacrylic acid in the polyacrylic acid aqueous solution is 2%; 3) Weigh 0.5%-1% of the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs prepared in step 1) and add them to 99%-99.5% polyacrylic acid aqueous solution, and uniformly disperse the sulfonic acid functionalized COFs or carboxylic acid functionalized COFs in the polyacrylic acid aqueous solution by ultrasound.

9. An application of a lithium battery negative electrode binder, characterized in that: The method of preparing a lithium battery using a lithium battery negative electrode binder according to any one of claims 1 to 7 comprises the following steps: S1: The active material, the lithium battery negative electrode binder according to any one of claims 1 to 7, and the conductive agent are mixed in a mass ratio of 7:2:1 for coating, and the coated copper foil is placed in a vacuum oven and dried at 120°C for 12 hours, and then sliced ​​to obtain a circular electrode sheet; S2: The circular electrode sheet obtained in step S1 is used as a working electrode, a lithium sheet is used as a reference electrode and a counter electrode, lithium hexafluorophosphate is used as an electrolyte, fluoroethylene carbonate is used as an electrolyte additive, and a polyvinylidene fluoride ceramic diaphragm is used as a diaphragm, and a lithium battery is assembled in a glove box filled with argon.

10. An application of a lithium battery negative electrode binder, characterized in that: The active material in step S1 is silicon carbon-1200, and the conductive agent in step S1 is carbon nanotube.